Penguatan Kesiapan Karier Dalam Program Kampus Mengajar Berdampak Di SMK Negeri 3 Makassar - Nabila Herman; Aswar Aswar; Syahrul Ramadan; Herdiananda Nurhidayah; Asyifa Atzanjani Syarif (PT Ininnawa Paramacitra Edu, 2026)
Graduates of vocational high schools (SMK) in Indonesia currently still face high unemployment. The main problem is the gap between the skills students have and the needs of the workforce, coupled with the fact that many students are not mentally prepared to graduate from school. In response to this, a team from Makassar State University, through the Impact Teaching Campus (KMB) program, conducted counseling guidance activities at SMK Negeri 3 Makassar. This activity aims to make students more prepared to p ursue a career in two ways: by recognizing personality through the RIASEC test and strengthening mental resilience. Involving 32 students from grades XI and XII, the activity was carried out in two stages: mapping career interests and an exciting seminar themed